Peningkatan Kesadaran dan Kepatuhan Hukum kepada Masyarakat Kampung Susiloharjo, Kelurahan Siswodipurjan, Kecamatan Boyolali, Kabupaten Boyolali Guna Mewujudkan Ketertiban Sosial - Pradoto, Waluyo Slamet; Laksito, FX. Hastowo Broto (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This service activity aims to increase legal awareness of the people of Susiloharjo village. Siswodipuran Village, Boyolali District. Bovolali Regency to create a law-abiding society so as to achieve social order. This community service activity was carried out at the Susiloharjo Citizens' Hall, with a total of 20 participants. The method used is a lecture and discussion method related to legal aspects that apply in Indonesia. The results of service activities show that the community in Susiloharjo village has demonstrated a positive legal culture by complying with regulations and committing minimal violations of the law or crimes. Apart from that, the public also paid attention to the material presented by the resource persons and provided comments regarding current law enforcement practices.